Neurotheology - the naturalistic conceptualization of religious experience - Kowalczyk, Kinga (Hybris, 2012)
The aim of this article is to test explanatory potential of neurotheology – interdisciplinary branch of science which main goal is to explain religious experience by using neuroimaging techniques as well as methods and terms of modern neurobiology. In the introductory part of this paper, author tries to present general historical background of neurotheology and its philosophical outline. Subsequently, in the first chapter, author analyses assumptions and implications of localisationism - which is one of the two fundamental trends in neurotheology - based on studies of two prominent researchers: M. Persinger and V.S. Ramachandran. Chapter one also highlights impact of so called sacred disease – epilepsy - on neurotheology. The next chapter is concerned with the second principal trend in neurotheology, namely, equipotentism. At this point author describes the advantages and disadvantages of this current through doing an analysis of Newberg’s and d’Aquili’s work. In the last part of the article, author attempts to draw conclusions about explanatory capabilities and limits of neurotheology. The finding is that neurotheology offers tools and mechanisms only for narrowly defined religious experience and it should not be implemented to study of religion per se.